2022
DOI: 10.1007/s11096-022-01475-8
|View full text |Cite
|
Sign up to set email alerts
|

Development, implementation and evaluation of a seven-day clinical pharmacy service in a tertiary referral teaching hospital during surge-2 of the COVID-19 pandemic

Abstract: Background Seven-day clinical pharmacy services in the acute sector of the National Health Service are limited. There is a paucity of evidential patient benefit. This limits investment and infrastructure, despite United Kingdom wide calls. Aim To optimise medicines seven-days a week during surge-2 of the COVID-19 pandemic through implementation of a seven-day clinical pharmacy service. This paper describes service development, evaluation and sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The PROTECTED-UK study reported a higher clinical intervention rate (to correct medication errors) by pharmacists on weekends compared to weekdays (33.6% vs 16.1%; p < 0.0001), with clinical interventions rated as moderate to high clinical impact in the majority of scenarios [5]. The utilisation of critical care pharmacists has repeatedly shown to lower ICU mortality, lower ICU length of stay, lower healthcare costs, and detect adverse drug events [3,5,20,29]. Extending the clinical pharmacy at the weekend provides an opportunity to extend these patient bene ts across a seven-day service.…”
Section: Seven-day Clinical Pharmacy Services Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PROTECTED-UK study reported a higher clinical intervention rate (to correct medication errors) by pharmacists on weekends compared to weekdays (33.6% vs 16.1%; p < 0.0001), with clinical interventions rated as moderate to high clinical impact in the majority of scenarios [5]. The utilisation of critical care pharmacists has repeatedly shown to lower ICU mortality, lower ICU length of stay, lower healthcare costs, and detect adverse drug events [3,5,20,29]. Extending the clinical pharmacy at the weekend provides an opportunity to extend these patient bene ts across a seven-day service.…”
Section: Seven-day Clinical Pharmacy Services Activitiesmentioning
confidence: 99%
“…Furthermore, the NHS England critical care service speci cation states that commissioned CCUs must align to GPICS guidelines [17]. In the UK, there is a good evidence base describing the CC pharmacy workforce and activities, especially clinical pharmacists, although there remains great variation in the delivery of the clinical pharmacy service, MDT ward round participation and 7-day clinical pharmacy services, despite evidence of bene t [18][19][20]. This is not the case for commissioned ECMO services, where no data exists for the clinical pharmacy workforce.…”
Section: Introductionmentioning
confidence: 99%
“…The CFIR is a conceptual, systematic and meta-theoretical approach that is used to assess the uptake of a program against key factors that have been shown to influence the implementation of complex programs [8][9][10]. The CFIR has been used to assess the implementation of health-related services, such as weight management [7], hospital care [11], chronic disease [12] and pharmacy services [13], and the implementation of social services, such as the introduction of intensive family-based therapy programs in the Australian state of Victoria [4].…”
Section: Introductionmentioning
confidence: 99%